2005
DOI: 10.1007/s11211-005-6825-1
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Bias and Inequity: Legitimizing Beliefs and Policy Attitudes

Abstract: Policy attitudes relating to group-based inequities are in many cases founded on tenuous legitimizing beliefs which are contradicted by empirical evidence. Policy issues, and their attendant legitimizing beliefs, are considered, including affirmative action, colorblindness/"racial privacy," hate crime legislation, samesex marriage, and, in greater depth, capital punishment and racial profiling. Primary themes underlying the legitimizing beliefs include denials that groupbased biases and inequities exist, overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
(33 reference statements)
2
28
0
2
Order By: Relevance
“…It is also consistent with research from outside behavioral psychology (e.g., Blendon, Benson, & Donelan, 1993;Glaser, 2005;Rabinowitz, Sears, Sidanius, & Krosnick, 2009). For instance, the present results indicated that more people valued legislation when it was framed as about a woman's right to choose vs. about abortion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is also consistent with research from outside behavioral psychology (e.g., Blendon, Benson, & Donelan, 1993;Glaser, 2005;Rabinowitz, Sears, Sidanius, & Krosnick, 2009). For instance, the present results indicated that more people valued legislation when it was framed as about a woman's right to choose vs. about abortion.…”
Section: Discussionsupporting
confidence: 90%
“…For example, past research has suggested that participants object to government intervention in the lives of its citizens and view affirmative action as such (Glaser, 2005). Similar to the finding with abortion and right-to-choose policy, the more "benign" phrase of equal rights produced non-discounting to a much lesser degree.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the theory assumes that individuals will engage in social action and work for the collective good if they develop a sense of critical consciousness (Gutierrez 1995). This is consistent with Glaser's (2005) findings that much of the basis for opposition to policies that redress inequality (such as affirmative action) derives from ideologies and beliefs that rationalize inequality and thereby justify the current system and status quo.…”
Section: Finding Food Justice: What Role For Academics?supporting
confidence: 86%
“…The issue of legitimating myths is most broadly explored by Glaser (2005), who considers such myths in a wide variety of policy settings, including affirmative action, hate crime legislation, same-sex marriage, capital punishment, racial profiling, and others. His essay examines how such myths are perpetuated in situations in which there are arguments for, and even empirical evidence of, their invalidity.…”
mentioning
confidence: 99%